CURRENT STATUS OF BIODIVERSITY IN SEMI-ARID AREAS OF SYRDARYA REGION AND STRATEGIES FOR ITS PRESERVATION (The New Uzbekistan Journal of Medicine, 2025)
This article analyzes the current status of plant biodiversity in semi-arid landscapes of Syrdarya region, the floristic composition of phytocenoses, ecological groups, and their adaptation to natural and anthropogenic factors. In the course of the research, the features of phytocenological observations, GIS technologies, remote sensing data, and ecological and bioindicator approaches were studied. The obtained analyzes show that due to drought, soil salinization, and anthropogenic pressure in the region, populations of some species are decreasing, and the degradation process of phytocenoses is intensifying. Priority areas for biodiversity preservation in the region have been developed.